Disappearing brain lesions, psychosis and epilepsy: a report of two cases. - Feinstein, A (1990)
The association between disappearing brain lesions, psychosis and epilepsy in two patients is reported for the first time. Mechanisms to explain the underlying pathogenesis are postulated.